A wide-bandgap perovskite monolayer film based on a sacrificial coordination strategy and a preparation method and application thereof
Patent Information
- Application Number
- CN202611052317.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-13
AI Technical Summary
但SAM存在固有缺陷:分子偶极矩较小,界面能级调控能力有限;引入苯环增强偶极矩虽能改善能级匹配,却会因疏水性降低前驱体浸润性;同时,SAM有限的厚度与不完全覆盖性,无法有效阻挡漏电流
[0018]有益效果:1)本发明通过牺牲配位策略,在ALD-Al2O3沉积过程中完整保护SAM结构,显著提升单分子层覆盖因子与锚定稳定性,解决了TMA破坏SAM的行业难题;
Smart Images

Figure CN122909993A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photovoltaic materials technology, specifically relating to a wide-bandgap perovskite thin film based on a sacrificial coordination strategy to regulate a monolayer, its preparation method, and its application. Background Technology
[0002] Wide-bandgap perovskite solar cells have become a research hotspot in the photovoltaic field due to their excellent photoelectric performance. In the device structure, the hole transport layer, located between the transparent electrode and the perovskite layer, plays a decisive role in the device performance: it is necessary not only to efficiently extract holes and suppress nonradiative recombination at the interface, but also to ensure good wettability to the precursor solution in order to prepare high-quality perovskite thin films.
[0003] Self-assembled monolayers (SAMs), as novel hole transport materials, possess advantages such as precisely controllable thickness and low parasitic absorption, and are typically anchored to the surface of ITO electrodes via phosphonic acid groups. However, SAMs have inherent drawbacks: their small molecular dipole moment limits their ability to modulate interfacial energy levels; while introducing benzene rings to enhance the dipole moment can improve energy level matching, it reduces precursor wettability due to hydrophobicity; furthermore, the limited thickness and incomplete coverage of SAMs cannot effectively block leakage current.
[0004] To address the aforementioned problems, existing technologies introduce nickel oxide (NiO). x The intermediate layer is used to improve wettability and block leakage current, but NiO x SAM (Solid Aluminum Oxide) readily aggregates to form porous films, and its multivalent defects can trigger interfacial recombination and redox reactions, impairing device stability. Atomic layer deposition (ALD) technology can grow dense and uniform Al2O3 films, possessing both high surface energy and carrier tunneling capability, without introducing additional defects. However, the key ALD precursor, trimethylaluminum (TMA), reacts chemically with the phosphonic acid anchoring group of SAM, weakening the binding strength between SAM and ITO. This leads to severe SAM desorption and a significant decrease in coverage factor during subsequent polar solvent processing, ultimately causing interfacial energy level disturbances.
[0005] Currently, how to fully preserve the structure and function of SAM while depositing dense Al2O3 thin films remains a technical challenge that urgently needs to be solved in this field. Summary of the Invention
[0006] Technical problem solved: To address the above-mentioned technical problems, this invention provides a wide-bandgap perovskite thin film based on a sacrificial coordination strategy to regulate the monolayer, its preparation method and application. By sacrificing coordination small molecules to protect the self-assembled monolayer, ALD-Al2O3 deposition and SAM structure can coexist stably, resulting in a wide-bandgap perovskite thin film with high crystal quality and low defect density, which significantly improves the photoelectric conversion efficiency and long-term stability of solar cells.
[0007] Technical solution: In a first aspect, the present invention provides a method for preparing wide-bandgap perovskite thin films based on a sacrificial coordination strategy to regulate the monolayer, comprising the following steps: S1. Preparation of sacrificial coordination complex monolayers: A mixed precursor solution containing a self-assembled monolayer (SAM) and sacrificial coordination small molecules was prepared, spin-coated onto a clean transparent conductive substrate, and annealed to obtain a SAM / sacrificial coordination small molecule composite hole transport layer. The self-assembled monolayer is one or more of the following: (2-(9H-carbazole-9-yl)ethyl)phosphonic acid, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [2-(3,6-diphenyl-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-diphenyl-9H-carbazole-9-yl)butyl]phosphonic acid, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid, and [4-(7H-dibenzocarbazole-7-yl)butyl]phosphonic acid. The sacrificial coordination molecule has the following general structural formula: , Where X is N or C; R1 is F, Cl, Br, I, -CF3, -CHF2, -OCF3, -C2F5, -C x H 2x+1 One of them, where x takes values from 0 to 6; R² is -C y H 2y+1 The value of y ranges from 0 to 6; S2, Atomic layer deposition of Al2O3 barrier layer: A stable substrate was obtained by growing Al2O3 thin films on a composite monolayer via atomic layer deposition using trimethylaluminum and water as precursors. S3, Preparation of wide-bandgap perovskite thin films: Preparation of FA 0.8 Cs 0.2 PbI 1.6 Br 1.4 The perovskite precursor solution was spin-coated onto a stable substrate, followed by gas quenching-assisted film formation and thermal annealing to obtain the target perovskite thin film.
[0008] Preferably, the doping concentration of the sacrificial coordination molecule is 1% to 10% of the molar amount of SAM; the concentration of the SAM precursor solution is 0.3 to 1.0 mg / mL, and the solvent is isopropanol or ethanol.
[0009] Preferred atomic layer deposition parameters are: deposition temperature 80–150℃, number of cycles 1–20; trimethylaluminum pulse time 0.02–0.1 s, water pulse time 0.02–0.1 s, and nitrogen purging time 5–30 s.
[0010] Preferred, FA 0.8 Cs 0.2 PbI 1.6 Br 1.4 The perovskite precursor solution solvent is a mixture of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 3:1 to 5:1, and the concentration of the perovskite precursor solution is 0.4 to 2 M. The spin coating speed is 1500-4500 rpm, the gas quenching gas pressure is 20 to 40 psi, the hot annealing temperature is 80 to 150℃, and the hot annealing time is 5 to 60 min.
[0011] In a second aspect, the present invention provides a wide-bandgap perovskite thin film based on a sacrificial coordination strategy to regulate the monolayer, wherein the wide-bandgap perovskite thin film is prepared by the preparation method described in the first aspect.
[0012] Preferably, the thickness of the wide-bandgap perovskite film is 100–1000 nm, and it has the characteristics of dense grains, few grain boundaries, no pinhole defects, and high crystallinity.
[0013] Thirdly, the present invention provides the application of the wide-bandgap perovskite thin film described in the second aspect in the fabrication of perovskite solar cells.
[0014] Preferably, the structure of the perovskite solar cell comprises, in sequence: a transparent conductive substrate, a composite monolayer, an ALD-Al2O3 layer, a wide-bandgap perovskite thin film, an electron transport layer, and an anode.
[0015] Furthermore, the electron transport layer is zinc oxide, PTAA, PBDB-T, PM6, PCBM, or C. 60 @BCP, one or more of tin oxide, with a thickness of 10–50 nm.
[0016] Furthermore, the anode is an Au, Ag, Al, Cu, carbon electrode or a PH1000 electrode, with a thickness of 10–200 nm.
[0017] Fourthly, the present invention provides a wide-bandgap perovskite solar cell comprising the wide-bandgap perovskite thin film described in the second aspect, with a photoelectric conversion efficiency ≥19.7%.
[0018] Beneficial effects: 1) This invention protects the SAM structure completely during ALD-Al2O3 deposition by using a sacrificial coordination strategy, significantly improving the monolayer coverage factor and anchoring stability, and solving the industry problem of TMA damaging SAM. 2) The wide-bandgap perovskite thin film prepared by this invention has dense grains, low defect density, no pinholes or grain boundary defects, and significantly improved crystallization quality; 3) The photoelectric conversion efficiency of the solar cell based on this thin film reaches 19.74%, the open-circuit voltage is 1.371 V, and the long-term working stability is improved by more than 50%; 4) It has strong process compatibility and a wide concentration window, and is suitable for various carbazole-based SAMs, which can be applied on a large scale to high-efficiency perovskite photovoltaic devices. Attached Figure Description
[0019] Figure 1 Comparison of SAM coverage factors before and after the sacrificial coordination strategy; Figure 2 P2pXPS spectra of SAM before and after sacrificial coordination strategy; Figure 3 SEM images of the perovskite thin films in the examples and comparative examples; Figure 4 Examples and comparative examples show the battery current-voltage curves; Figure 5 Current-voltage curves of batteries with different doping concentrations; Figure 6 This is a DLCP carrier concentration-depth distribution map before and after battery aging. Detailed Implementation
[0020] The present invention will be described in detail below with reference to specific embodiments: Unless otherwise specified, all raw materials used in the embodiments of this invention are commercially available. Specifically: ITO conductive glass and nickel oxide were purchased from Liaoning Youxuan New Energy Technology Co., Ltd.; Ph-4PACz and 6-hydroxy-4-trifluoromethylnicotinic acid (HTFNA) were purchased from TCI Corporation of Japan; cesium iodide, formamidine iodide, lead iodide, lead bromide, and C... 60 BCP was purchased from Xi'an Yuri Solar Energy Technology Co., Ltd.; DMF and DMSO were purchased from Beijing Bailingwei Technology Co., Ltd.
[0021] The perovskite thin-film solar cell device structure provided by this invention is as follows: ITO conductive glass / hole transport layer / ALD-Al2O3 layer / perovskite active layer / electron transport layer / anode. Specifically, the hole transport layer is Ph-4PACz and the electron transport layer is C. 60 @BCP composite layer, anode is silver.
[0022] Solution preparation: Basic hole transport layer [4-(3,6-diphenyl-9H-carbazole-9-yl)butyl]phosphonic acid (Ph-4PACz) solution: Weigh 1.2 mg of Ph-4PACz powder, add 4 mL of ethanol, stir at 30℃ for 2 h, and set aside for later use; Perovskite precursor solution: 147.5 mg PbI₂, 260.6 mg PbBr₂, 52.0 mg CsI, and 137.5 mg FAI were dissolved in 1 mL of a mixed solvent (DMF:DMSO = 4:1, volume ratio) to prepare a 1.0 M concentration of FAI. 0.8 Cs 0.2 PbI 1.6 Br 1.4 The solution was stirred at 60°C for 4 hours and then filtered through a 0.45 mm PTFE organic filter before use. Example 1
[0023] A method for preparing a hole transport layer based on a sacrificial coordination strategy, comprising the following steps: (1) Preparation of mixed precursor solution: Using isopropanol as solvent, prepare a Ph-4PACz solution with a concentration of 0.5 mg / mL, and add 5% molar fraction of sacrificial coordination molecule HTFNA, and stir evenly; (2) Substrate treatment: Take the cleaned ITO / FTO conductive glass and spin-coat the above mixed solution at 3000 rpm for 30 s; after spin-coating, anneal at 100℃ for 10 min to obtain the sacrificial coordination hole transport layer (SC-Ph-4PACz). (3) ALD-Al2O3 deposition: The substrate with the hole transport layer was placed in the atomic layer deposition equipment, and Al2O3 was deposited at 100°C using trimethylaluminum (TMA) and deionized water as precursors. Process parameters: TMA pulse time 0.05 s, water pulse time 0.05 s, nitrogen purging time 15 s, 5 cycles, to obtain SC-Ph-4PACz / ALD-Al2O3 functional substrate.
[0024] Comparative Example 1 Except for the absence of HTFNA, the remaining steps were exactly the same as in Example 1, and a pure Ph-4PACz / ALD-Al2O3 substrate was prepared.
[0025] X-ray photoelectron spectroscopy (XPS) was performed on the samples of Example 1 and Comparative Example 1. The coverage factor of the self-assembled monolayer was calculated by the ratio of the characteristic peak areas of P 2p and In 3d. Figure 1 The figure shows a comparison of the coverage factor of self-assembled monolayers on the ITO surface before and after employing a sacrificial coordination strategy. XPS results show that, without the sacrificial coordination strategy, the coverage factor of the pure Ph-4PACz film after TMA exposure and DMF rinsing treatment increased from 43 × 10⁻⁶. -3 It decreased significantly to 28.6×10 -3This indicates that TMA chemically reacts with the phosphonic acid anchoring groups of SAM, severely weakening the binding strength between SAM and ITO, leading to significant desorption during polar solvent treatment. In contrast, the SC-Ph-4PACz film employing a sacrificial coordination strategy, after the same TMA exposure and DMF rinsing treatment, showed a coverage factor that increased from 56.8 × 10⁻⁶. -3 It only decreased slightly to 49×10 -3 This demonstrates that HTFNA molecules, through their preferential coordination with TMA via their hydroxyl groups, effectively protect the phosphonic acid anchoring groups of Ph-4PACz from chemical degradation by TMA. This significantly enhances the anchoring stability of SAM during ALD-Al2O3 deposition and subsequent polar solvent processing, providing a structurally sound interfacial basis for achieving high-quality perovskite film deposition. Example 2
[0026] The difference from Example 1 is that the ITO / FTO substrate is replaced with a silicon wafer, otherwise it is the same as Example 1.
[0027] Comparative Example 2 The difference from Comparative Example 1 is that the ITO / FTO substrate is replaced with a silicon wafer, otherwise it is the same as Comparative Example 1.
[0028] XPS high-resolution P 2p spectroscopy was performed on the samples of Example 2 and Comparative Example 2, as follows: Figure 2 The image shows the high-resolution P2p spectra of the self-assembled monolayers before and after employing the sacrificial coordination strategy. XPS results indicate that the P2p characteristic peak of the Ph-4PACz film without the sacrificial coordination strategy shifts significantly towards higher binding energies after TMA exposure. This suggests that TMA coordinates with the oxygen atoms in the phosphonic acid groups, forming a PO-Al(CH3)3 complex, which reduces the electron cloud density around the phosphine atoms, leading to an increase in their binding energy. In contrast, the P2p characteristic peak position of the SC-Ph-4PACz film employing the sacrificial coordination strategy remains essentially unchanged under the same TMA exposure conditions. This indicates that HTFNA molecules preferentially coordinate with TMA, effectively preventing chemical attack by TMA on the Ph-4PACz phosphonic acid anchoring groups, protecting the chemical structural integrity of the SAM, and providing a stable interfacial foundation for the subsequent high-quality deposition of perovskite films. Example 3
[0029] Wide-bandgap perovskite films were prepared on the SC-Ph-4PACz / ALD-Al2O3 substrate prepared in Example 1: Using 1.0 mol / L FA 0.8 Cs 0.2 PbI 1.6 Br 1.4Precursor solution (solvent DMF:DMSO = 4:1); Spin coating: Spin coating speed 3000 rpm, 10 s after spin coating begins, gas quenching is used to assist crystallization (air gun distance 4 cm from film, nitrogen pressure 20 psi, purging for 15 s). Annealing treatment: Anneal at 100℃ for 30 min to obtain a dense, high-crystallinity wide-bandgap perovskite film.
[0030] Comparative Example 3 Compared to Example 3, only the substrate was replaced with Ph-4PACz / ALD-Al2O3 of Comparative Example 1, and the rest of the process was exactly the same.
[0031] The buried interface and top surface of the perovskite films prepared in Example 3 and Comparative Example 3 were observed by SEM, as follows: Figure 3 As shown in the figure, SEM results indicate that the buried interface of the perovskite film without the sacrificial coordination strategy exhibits numerous pinholes and defects, with small and unevenly distributed grains; its top surface also shows many grain boundaries and pores, resulting in poor film density. In contrast, the buried interface of the perovskite film using the sacrificial coordination strategy is significantly smoother and denser, with a marked reduction in the number of pinholes and an increase in grain size; its top surface shows more compact grain packing, a significant reduction in the number of grain boundaries, and a substantial improvement in film uniformity. These results demonstrate that the sacrificial coordination strategy, by protecting the anchoring integrity of the self-assembled monolayer and improving the substrate surface energy, promotes uniform nucleation and growth of perovskite at the buried interface, effectively suppressing the formation of defects at the buried interface, thereby obtaining a perovskite film with higher overall crystal quality and greater density. Example 4
[0032] Device encapsulation was completed on the perovskite thin film prepared in Example 3: (1) Vacuum evaporation of electron transport layer: C 60 The deposition rate was 0.2 Å / s, and the thickness was 20 nm. The deposition rate of BCP was 0.2 Å / s, and the thickness was 6 nm. (2) Evaporation of metal anode: Ag electrode thickness 100 nm, resulting in an effective area of 0.0628 cm². 2 Wide-bandgap perovskite solar cells.
[0033] Comparative Example 4 Compared to Example 4, only the perovskite film was replaced with the sample of Comparative Example 3, and the rest of the process was exactly the same.
[0034] Comparing the performance of the perovskite solar cells in Example 4 and Comparative Example 4, we obtain... Figure 4 Current-voltage curve of perovskite solar cell (effective area 0.0628 cm²) 2(See Table 1) and the light intensity is AM1.5G, 100 mW / cm². 2 .
[0035] Table 1 Comparison of photovoltaic performance parameters of wide-bandgap perovskite solar cells
[0036] from Figure 4 As shown in Table 1, the open-circuit voltage and fill factor of the wide-bandgap perovskite solar cell are significantly improved after adopting the sacrificial coordination strategy, and the device efficiency reaches 19.74% (effective area is 0.0628 cm²). 2 Compared to the control device that did not employ the sacrificial coordination strategy, the open-circuit voltage increased by 0.029 V, and the current density increased by 0.54 mA / cm². 2 The fill factor was improved by 1.63%. Research shows that by introducing sacrificial coordination molecules into the self-assembled monolayer precursor solution, utilizing the preferential coordination of their hydroxyl groups with the trimethylaluminum precursor in atomic layer deposition, the phosphonic acid anchoring groups of the self-assembled monolayer are effectively protected from chemical reaction damage, preventing SAM desorption during subsequent polar solvent processing. Simultaneously, HTFNA inhibits the self-aggregation of SAM molecules through hydrogen bonding, improving the hole transport layer coverage and interfacial energy level matching, promoting high-quality crystallization of the perovskite film, and reducing interfacial non-radiative recombination losses. The PCE of devices without the sacrificial coordination strategy differed by 1.4% compared to those using this strategy, demonstrating the unique advantages of the sacrificial coordination strategy in protecting the structural integrity of the self-assembled monolayer and improving the photovoltaic performance of wide-bandgap perovskite solar cells. Example 5
[0037] Compared with Example 4, this example only adjusts the HTFNA doping ratio, which is 3 mol%; the rest of the preparation process and parameters are exactly the same as in Example 4, and the corresponding solar cell is obtained. Example 6
[0038] Compared with Example 4, this example only adjusts the HTFNA doping ratio, which is 10 mol% in this example; the rest of the preparation process and parameters are exactly the same as in Example 4, and the corresponding solar cell is obtained.
[0039] Comparing the performance of the perovskite solar cells in Examples 4-6, we obtain Figure 5 Current density-voltage curves of wide-bandgap perovskite solar cells doped with different proportions of HTFNA (effective area 0.0628 cm²) 2 (See Table 2) for light intensity of AM1.5G, 100 mW / cm². 2 .
[0040] Table 2 Comparison of photovoltaic performance parameters of wide-bandgap perovskite solar cells with different proportions of HTFNA doping
[0041] from Figure 5 As shown in Table 2, when the HTFNA doping ratio is in the range of 3% to 10%, the wide-bandgap perovskite solar cells all exhibit excellent photovoltaic performance, with open-circuit voltages exceeding 1.35 V and device efficiencies exceeding 19.0%. This demonstrates that the sacrificial coordination strategy has a wide doping concentration window, which is beneficial for process tolerance and large-scale production. Among them, the device performance is optimal when the HTFNA doping ratio is 5%, with an open-circuit voltage of 1.371 V, a fill factor of 85.38%, and a photoelectric conversion efficiency of 19.74%.
[0042] To evaluate the operational stability of the device, stability tests were conducted. The perovskite solar cell fabrication method is described in Example 4 and Comparative Example 4.
[0043] The prepared wide-bandgap perovskite solar cells were aged for 300 h at 25°C under a nitrogen atmosphere and under continuous maximum power point tracking conditions, and then subjected to drive-level capacitance analysis (DLCP) tests. Figure 6 The figures show the DLCP carrier concentration-depth distribution curves before and after aging for perovskite solar cells employing the sacrificial coordination strategy and those without. Figure 6 As shown, the control device without the sacrificial coordination strategy had a carrier concentration of 1.44 × 10⁻⁶ at the hole transport layer / perovskite interface before aging. 14 cm -3 After 300 hours of maximum power point tracking aging, the carrier concentration at the interface dropped sharply to 3.72 × 10⁻⁶. 13 cm -3 The concentration decreased by approximately 74%. This indicates that under prolonged operating conditions, the unprotected device experiences partial desorption of SAM at the interface due to the chemical reaction of TMA with the phosphonic acid anchoring groups of SAM. This leads to a continuous deterioration of the contact quality at the hole transport layer / perovskite heterostructure interface, a significant increase in the interface defect state density, and a substantial decrease in the effective carrier concentration in the depletion region. In contrast, the target device employing the sacrificial coordination strategy had a carrier concentration of 4.63 × 10⁻⁶ at the interface before aging. 14 cm -3 After aging under the same conditions, it can still maintain 2.93×10 14 cm -3The decrease was only 36%. This indicates that the sacrificial coordination strategy, through preferential coordination of HTFNA molecules with TMA, effectively protects the anchoring structural integrity of the SAM, enhances the adhesion stability and energy level matching of the hole transport layer / perovskite heterointerface, and effectively suppresses the accumulation of interface defects and the formation of carrier trapping centers under long-term operating conditions, thereby significantly improving the operational stability of the interface. These results demonstrate that the sacrificial coordination strategy can enhance the structural and electrical stability of the hole transport layer / perovskite interface from the source, providing a reliable interface engineering solution for realizing long-lifetime, wide-bandgap perovskite solar cells.
[0044] Sacrificial coordination small molecules have the following general structural formula: , Where X is N or C; R1 is F, Cl, Br, I, -CF3, -CHF2, -OCF3, -C2F5, -C x H 2x+1 One of them, where x takes values from 0 to 6; R² is -C y H 2y+1 The value of y ranges from 0 to 6; all of the above sacrificial coordination molecules can achieve the above functions.
[0045] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing wide-bandgap perovskite thin films with monolayer controlled by a sacrificial coordination strategy, characterized in that, Includes the following steps: S1. Prepare a mixed precursor solution containing a self-assembled monolayer and sacrificial coordination small molecules, spin-coat it onto a transparent conductive substrate, and anneal it to obtain a composite hole transport layer. The self-assembled monolayer is one or more of the following: (2-(9H-carbazole-9-yl)ethyl)phosphonic acid, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [2-(3,6-diphenyl-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-diphenyl-9H-carbazole-9-yl)butyl]phosphonic acid, [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid, and [4-(7H-dibenzocarbazole-7-yl)butyl]phosphonic acid. The sacrificial coordination molecule has the following general structural formula: , Where X is N or C; R1 is F, Cl, Br, I, -CF3, -CHF2, -OCF3, -C2F5, -C x H 2x+1 One of them, where x takes values from 0 to 6; R² is -C y H 2y+1 The value of y ranges from 0 to 6; S2. An Al2O3 barrier layer is grown on a composite monolayer by atomic layer deposition. S3, Spin Coating FA 0.8 Cs 0.2 PbI 1.6 Br 1.4 A perovskite precursor solution is subjected to gas quenching and hot annealing to obtain a wide-bandgap perovskite thin film.
2. The preparation method according to claim 1, characterized in that: The concentration of the sacrificial coordination molecule doping is 1 to 10% of the molar amount of the self-assembled monolayer; the concentration of the self-assembled monolayer precursor solution is 0.3 to 1.0 mg / mL, and the solvent is isopropanol or ethanol.
3. The preparation method according to claim 1, characterized in that: Atomic layer deposition parameters: deposition temperature 80–150℃, number of cycles 1–20; trimethylaluminum pulse time 0.02–0.1 s, water pulse time 0.02–0.1 s, nitrogen purging time 5–30 s.
4. The preparation method according to claim 1, characterized in that: FA 0.8 Cs 0.2 PbI 1.6 Br 1.4 The perovskite precursor solution solvent is a mixture of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 3:1 to 5:1, and the concentration of the perovskite precursor solution is 0.4 to 2 M. The spin coating speed is 1500-4500 rpm, the gas quenching gas pressure is 20 to 40 psi, the hot annealing temperature is 80 to 150℃, and the hot annealing time is 5 to 60 min.
5. A wide-bandgap perovskite thin film with monolayer controlled by a sacrificial coordination strategy, characterized in that: The wide-bandgap perovskite film is prepared by the preparation method according to any one of claims 1-4, and the thickness of the wide-bandgap perovskite film is 100-1000 nm.
6. The application of the wide-bandgap perovskite thin film according to claim 5 in the preparation of perovskite solar cells.
7. The application according to claim 6, characterized in that, The perovskite solar cell structure comprises, in sequence: a transparent conductive substrate, a composite monolayer, an ALD-Al2O3 layer, a wide-bandgap perovskite thin film, an electron transport layer, and an anode.
8. The application according to claim 7, characterized in that: The electron transport layer is zinc oxide, PTAA, PBDB-T, PM6, PCBM, C 60 @BCP, one or more of tin oxide, with a thickness of 10–50 nm.
9. The application according to claim 7, characterized in that: The anode is an Au, Ag, Al, Cu, carbon electrode or a PH1000 electrode, with a thickness of 10–200 nm.
10. A wide-bandgap perovskite solar cell comprising the wide-bandgap perovskite thin film of claim 5.